Mechanical Behaviour of Ordered and Disordered Calcium Silicate Hydrates under Shear Strain Studied by Atomic Scale Simulations - M. Jennings, H; Masoero, E; Lopez-Arbeloa, I; Manzano, H (Mechanics and Physics of Creep, Shrinkage, and Durability of Concrete, 2013)
The C-S-H gel is the main constituent of cement, up to 70% of the final material. It is the phase that gives cohesion to the material and is mainly responsible for cement's properties, including creep. Understanding the intrinsic mechanical properties of the C-S-H gel and how it responds to applied load is, therefore, of vital importance for the design of the new generation of Portland Cement. However, the heterogeneous nature and characteristic length scale of the C-S-H gel makes an experimental determination of its properties very challenging. Therefore, atomic scale simulations are a valuable alternative to investigate the atomic scale forces and processes that govern creep and shrinkage. In this work, we study the mechanical processes that take place when the solid C-S-H is subject to a shear strain, using reactive force field molecular simulations. We have chosen two systems to model the C-S-H gel: the perfect mineral tobermorite and the glass-like C-S-H model developed by Pellenq, et. al. (Pellenq, et. al., 2009). First, we have computed the elastic properties of both models. Second, we investigate the global and local stresses generated in the systems under large deformations, with the aim to understand the atomic forces that govern the mechanical response of the structures. The obtained results help to understand the changes that happen in the C-S-H gel under load.